2007
DOI: 10.1111/j.1467-9450.2007.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in work values among male and female nurses and engineers

Abstract: Gender related changes of work values were analyzed in a longitudinal questionnaire study of 173 male and 48 female engineers and 353 female and 31 male nurses at three measurement occasions covering about four and half years from the end of their vocational education. At all occasions, Social relations were rated as more important by women than by men and Altruism was given higher ratings by the nurses than by the engineers. Within both occupations women's mean Altruism ratings were higher than men's mean rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
4
34
1
2
Order By: Relevance
“…These results are inline with previous research which indicates that males ask for more influence and authority and opportunity to be creative while females prefer higher level of independence and privacy (Bayrkova, 2015;Ryckman, & Houston, 2003;Martin & Osterling, 2014, Chen & Kao, 2012Lyons, Higgins, & Duxbury, 2010;Hagström & Kjellberg, 2007). However, Jordanian culture is a masculine one, and may affect our results and influence males to value jobs that have higher financial rewards as females are not expected to provide financial help to the family, like the western culture, but males are.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results are inline with previous research which indicates that males ask for more influence and authority and opportunity to be creative while females prefer higher level of independence and privacy (Bayrkova, 2015;Ryckman, & Houston, 2003;Martin & Osterling, 2014, Chen & Kao, 2012Lyons, Higgins, & Duxbury, 2010;Hagström & Kjellberg, 2007). However, Jordanian culture is a masculine one, and may affect our results and influence males to value jobs that have higher financial rewards as females are not expected to provide financial help to the family, like the western culture, but males are.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, research indicted that there are differences among males and females in work preferences (Ryckman & Houston, 2003). A study conducted by (Hagström & Kjellberg, 2007) indicated that females rated Social relations and Altruism more important. Additionally, females' ratings of Benefits and career development and Influence were higher than males.…”
mentioning
confidence: 99%
“…Despite these considerations, Hagstom & Kjellberg [15] found that both men and women in nursing put altruism first but men had higher scores at graduation for extrinsic factors. Over the first four years of work women nurses increased their value on extrinsic factors such as benefits and career and influence resulting in no gender differences.…”
Section: Background Motivationmentioning
confidence: 99%
“…is rich (Gibson and Schwartz, 1998;Schwartz, 2012;Ueda and Ohzono, 2013), the literature indicates that there is a lack of knowledge and effective investigation about the relationship between personal values and "profession" variable. Indeed, the limited research which concerned this issue, considered personal values in terms of specific characteristics of the profession and did not compare the personal values in different professions (Dinger, Thatcher and Stepina, 2010;Chang, Choi, and Kim , 2008;Cooman et al, 2008;Hegney et al, 2006;Hagstrom and Kjellberg, 2007). Values are placed at the center of cultural differences (Hofstede, 1980), and cultural differences exist not only at national or organizational levels, but also at the professional level.…”
Section: Introductionmentioning
confidence: 99%